System design and mechatronics of an air supply station for air-powered scooters. (August 2016) - Hung, Yi-Hsuan; Chen, Jian-Hao; Wu, Chien-Hsun; Chen, Syuan-Yi
Highlights: An air supply station with mechanical and electrical systems was built. Two operation modes were designed for charging air bottles. An air-powered scooter was used to evaluate the design specifications and charging performance. Results confirm that the station produced high-pressure air for vehicles. Theoretical analysis and performance simulation will be conducted in the future. Abstract: This study developed an air supply station for air-powered scooters. The station comprised mechanical and electrical systems. The key components of the mechanical system were a high-power air compressor, low-pressure cylinder, pneumatic boosting cylinder, high-pressure accumulator, and target tank. The electrical system comprised pressure sensors, air flow sensors, and control circuits, which were equipped adequately for the air charge. An air-powered scooter was used to evaluate the design specifications and charging performance of the station, and the scooter was tested on a chassis dynamometer to assess performance during a modified standard driving cycle. The experimental results confirmed that the air supply station can produce high-pressure air for air-powered vehicles. The station design can guide the development of similar technology by companies in the transportation and green energy industries. Future research will conduct a theoretical analysis by modeling and simulating the performance of the air station and air scooter. Graphical abstract: